Crimson warning a Lady Emily mystery - Alexander, Tasha (New York Minotaur Books, 2011)
Anticipating a London season of dancing and campaigning for women's rights, Lady Emily Hargreaves investigates a blackmailing vandal who splashes red paint on the homes of elite citizens before revealing their scandalous secrets.
115267
Keywords: Hargreaves, Emily, -- Lady (Fictitious character) -- Fiction; 1800-1899; Upper class -- England -- Fiction; Secrets -- Fiction; Manners and customs; Mayfair (London, England) -- Fiction; England -- Social life and customs -- 19th century -- Fiction; England; England -- London -- Mayfair; Mayfair (London, England) -- Fiction; Historical fiction; Mystery fiction; Fiction; Detective and mystery fiction